(untitled) (Bangladesh Journal of Urology, 2026)
The management of upper tract urothelial carcinoma (UTUC), which represents 5–10% of urothelial tumours and has traditionally been treated with radical nephroureterectomy with bladder cuff excision (RNU), has undergone significant transformation over the past two decades due to concerns regarding morbidity and renal functional decline. This review evaluates evolving understanding of risk factors distinguishing UTUC from bladder cancer, advances in diagnostic evaluation, the development of risk-stratification models, and the emergence of kidney-sparing strategies, chemoablation, and precision oncology. Recent literature highlights improvements in CT urography, high-definition and image-enhanced ureteroscopy, refined biopsy tools, and molecular diagnostics, all of which have enhanced diagnostic accuracy and enabled more precise risk stratification. These innovations support safe use of kidney-sparing surgery, including endoscopic ablation and segmental ureterectomy in low-risk UTUC, achieving oncologic outcomes comparable to RNU while preserving renal function, while topical chemoablation agents such as mitomycin gel (UGN-101) further expand renal-preserving options. For high-risk or metastatic disease, perioperative systemic chemotherapy, immune checkpoint inhibitors, and antibody drug conjugates now play an increasing role, though lifelong surveillance remains essential due to high recurrence rates in the bladder and contralateral tract. Overall, UTUC management has shifted from a uniform radical approach toward a precision-based, risk-adapted paradigm that balances oncologic control with renal preservation, with future directions focused on refining molecular biomarkers, validating kidney-sparing approaches in higher-risk cohorts, and expanding targeted systemic therapies. Bangladesh J. Urol. 2025; 28(2): 119-127